Implementasi Kurikulum Merdeka pada SMP Negeri 1 Karangtanjung Kabupaten Pandeglang - Rozikin; Kandung Sapto Nugroho (PANDITA: Interdisciplinary Journal of Public Affairs, 2025)
This study aims to examine the process of implementing the Merdeka Curriculum at SMP Negeri 1 Karangtanjung, to identify the challenges faced by teachers and the school in its implementation, as well as the strategies applied to overcome these challenges in order to improve the quality of learning. The research method used is qualitative with an in-depth interview approach involving various key informants, such as the principal, the vice principal in charge of curriculum, cross-subject teachers, administrative staff, the school committee, and school supervisors. The results show that the implementation of the Merdeka Curriculum is carried out collaboratively and in a structured manner with the principal playing a central role in facilitating training, coordination, and supervision. However, there are several main challenges including teacher readiness and adaptation, limited facilities and infrastructure, administrative obstacles, and a shift in school culture. Several strategies have been implemented, including enhancing teacher capacity through continuous training, improving coordination among stakeholders, simplifying administration, and strengthening an adaptive work culture. Synergistic implementation among school stakeholders is considered crucial in improving the quality of learning in accordance with the values of the Profile of Pancasila Students.